2006
DOI: 10.1186/1471-2431-6-3
|View full text |Cite
|
Sign up to set email alerts
|

A reference frame for blood volume in children and adolescents

Abstract: Background: Our primary purpose was to determine the normal range and variability of blood volume (BV) in healthy children, in order to provide reference values during childhood and adolescence. Our secondary aim was to correlate these vascular volumes to body size parameters and pubertal stages, in order to determine the best normalisation parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 12 publications
3
62
0
Order By: Relevance
“…Some evidence suggests that it is distributed in plasma volume (21), which is correlated to lean body mass and therefore, closely related to height (22). The proportion of lean body mass varies between boys and girls in that, on average, girls have higher body fat percentages than their boy counterparts (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that it is distributed in plasma volume (21), which is correlated to lean body mass and therefore, closely related to height (22). The proportion of lean body mass varies between boys and girls in that, on average, girls have higher body fat percentages than their boy counterparts (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the volume of distribution of BTP in the body, a pharmacokinetic study of recombinant human BTP in canines found evidence to suggest that BTP is distributed in plasma (21). Noting the relationship between lean body mass and plasma volume (22) and differences in the proportions of lean body mass between boys and girls (23), we hypothesized that sex would influence BTP. The purposes of our study were to investigate if sex affects BTP and if so, develop new formulas to calculate GFR in boys and girls on the basis of our BTP measurements.…”
Section: Introductionmentioning
confidence: 99%
“…According to Feldschuh and Enson [2] , use of the deviation of the TBW from the ideal body weight is the preferred reference method RESEARCH ARTICLE for predicting TBV. In a study of 77 children aged 18 years and under, Raes et al [4] used LBM as a normalizing constant for TBV and found it to be the best index of normalization from among TBW, BSA, LBM, and BMI, and it was not affected by gender differences. However, LBM is not always easy to measure and the equations used by them [4] to compute LBM may not always be applicable.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/029454 doi: bioRxiv preprint first posted online from the work of Raes et al (2006), R and RBC were taken from Castriota-Scanderbeg et al…”
mentioning
confidence: 99%